A promising new catalyst family for enantioselective cycloadditions involving allenes and imines: chiral phosphines with transition metal-CH2-P: linkages - Scherer, Alexander; Gladysz, John A. (Tetrahedron Letters, 2006)
The racemic rhenium-containing phosphine (η-CH)Re(NO)(PPh)(CHPPh) (3) catalyzes the [3+2] cycloaddition of HCdouble bond, longCdouble bond, longCHCOEt and N-tosyl imines ArCHdouble bond, longNTs in CH (RT, 1 d, 20 mol %) to give 2-aryl-3-carbethoxy-3-pyrrolines (Ardouble bond, longp-CHX (X = H, NO, OMe, Me, Cl, Br), 2-furyl; 95-84% isolated). Similar reactions with enantiopure (S)-3 are conducted in CHCl at -30 °C (8 d) to maximize enantioselectivities (60-51% ee; 93-90% isolated). © 2006 Elsevier Ltd. All rights reserved.